2022
DOI: 10.3389/fnins.2022.962901
|View full text |Cite
|
Sign up to set email alerts
|

Fmrp regulates neuronal balance in embryonic motor circuit formation

Abstract: Motor behavior requires the balanced production and integration of a variety of neural cell types. Motor neurons are positioned in discrete locations in the spinal cord, targeting specific muscles to drive locomotive contractions. Specialized spinal interneurons modulate and synchronize motor neuron activity to achieve coordinated motor output. Changes in the ratios and connectivity of spinal interneurons could drastically alter motor output by tipping the balance of inhibition and excitation onto target motor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…An earlier study by the same group analyzed metabolic indicators in Fmr1 KO mice 58 and found a lack of differences in glucose levels, which is in agreement with our study, but reported differences in serum lipid profile, leptin and insulin. Our study may be in agreement with a study using a zebrafish model of Fmr1 deletion, that determined developmental defects in the motor cortex, which may lead to changes in locomotion 59 . Also in agreement with our results here, decreased locomotion in the Fmr1 KO mice on the C57 background was reported before, in a report that demonstrated that reduced movement is due to reduced forward locomotion and bout onsets 43 .…”
Section: Discussionsupporting
confidence: 92%
“…An earlier study by the same group analyzed metabolic indicators in Fmr1 KO mice 58 and found a lack of differences in glucose levels, which is in agreement with our study, but reported differences in serum lipid profile, leptin and insulin. Our study may be in agreement with a study using a zebrafish model of Fmr1 deletion, that determined developmental defects in the motor cortex, which may lead to changes in locomotion 59 . Also in agreement with our results here, decreased locomotion in the Fmr1 KO mice on the C57 background was reported before, in a report that demonstrated that reduced movement is due to reduced forward locomotion and bout onsets 43 .…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, electrical coupling remains influential in more mature stages 48,49,74 , which suggests gap junctions could exert a persistent influence on hyperactivity in this FXS model. The emergence of chemical neurotransmission may also contribute to hyperactive locomotion phenotypes in FXS, as we've previously shown reduced expression of inhibitory synaptic machinery in fmr1 embryos at the end of embryogenesis 50 . Therefore, inhibitory INs in our FXS model may have reduced influence as locomotive activity progresses into more complex swimming behavior.…”
Section: Discussionmentioning
confidence: 95%
“…To test this possibility, we used an antibody raised against the neuronal gap junction protein Connexin 36 (Cx36), which detects Connexins encoded by multiple genes in zebrafish 48,49 . We detected Cx36 expression in whole-mount wild-type and fmr1 mutant embryos expressing the mnx1:EGFP transgene in these experiments to clearly label early motor units (Figure 6A,B), and used a three-dimensional surface modeling strategy to distinguish Cx36 punctal expression that was specifically localized to motor circuit neurons 50 . We first examined Cx36 expression at 17 hpf, just prior to most MN axogenesis and the initiation of spontaneous behavior, finding no change in Cx36 density on mnx1 + somata in fmr1 embryos, when normalized to the relative volume of mnx1:EGFP (Figure 6B,C).…”
Section: Increased Expression Of Connexin 36 In the Absence Of Fmrp I...mentioning
confidence: 99%
See 1 more Smart Citation